ROLE OF RADIOSURGERY IN ARTERIOVENOUS MALFORMATIONS - Ahmed, Syed Ijlal; Javed, Gohar; Uneeb, Saher Naseeb; Bareeqa, Syeda Beenish; Haider, Manaal; Samar, Syeda Sana; Ans, Armghan Haider; Shera, Muhammad Tayyab (Journal of Ayub Medical College Abbottabad, 2018)
Background: Intracranial arteriovenous malformations (AVMs) consist of an abnormal nidus of blood vessels that shunt blood directly from an artery to a vein and thereby bypass an intervening capillary bed. AVMs may be found as an incidental finding. They may be associated with intracranial haemorrhage, seizures, headaches or neurological deficits. There are different treatment options for AVM. These include observation, microsurgery, Stereotactic radio surgery (SRS), endovascular embolization and intensity modulated radiotherapy (IMRT). Method: Data was collected using searching engines like Pubmed, Google scholar, Embase, Cinahl and Medline. MeSH and Non-MeSH terms were used like Arterio-venous malformations, microsurgery, endovascular embolization. Results: Multiple interventional radiosurgical techniques have been introduced in recent years. The most effective and least risk-associated methods are Stereotactic radiosurgery, Microsurgery, Embolization and Intensity modulated radiotherapy (IMRT). However, the outcome of such treatment modalities depends upon Site of malformation, grade of AVM, patient's age/gender, dose and volume of radiosurgery. Digital substraction angiography (DSA) and MR angiography (MRA) are most suitable methods for the follow-up of AVMs. Conclusion: Stereotactic radiosurgery is the most suitable technique for AVMs considering the good prognosis and the risks associated with this procedure. However, large AVMs require multi-disciplinary approach for better results. Keywords: Arterio-venous malformations; stereotactic radio-surgery, microsurgery; endovascular embolization